Stability and Stabilization for a Class of Semilinear Fractional Differential Systems. (30th March 2020) - Ibrahim, Badawi Hamza Elbadawi; Dong, Qixiang; Zhang, Zhengdi
Abstract : This paper considers a class of semilinear fractional-order systems with Caputo derivative. New conditions ensuring asymptotic stability and stabilization of fractional systems with the fractional order between 0 and 2 are proposed. The analysis is based on a property of convolution and asymptotic properties of Mittag-Leffler functions. Some numerical examples are provided to illustrate the feasibility and validity of the proposed approach.